Hubungan Antara Kebutuhan Belajar dengan Minat Belajar Peserta Diklat Di BBPPKS Padang - Ranty Sevani Muder; Lili Dasa Putri (Jurnal Family Education, 2023)
This research is motivated by the low interest in learning of students caused by not achieving learning needs. This study aims to (1) describe the learning needs (2) describe the learning interests of the training participants (3) look at the relationship between learning needs and the learning interests of the training participants at BBPPKS Padang. This study uses a quantitative approach with a correlational type. The research population is training participants registered at BBPPKS Padang in 2023, totaling 102 people. The sampling technique used cluster random sampling which was taken 50% of the population totaling 31 people. The data collection technique is a questionnaire and the data collection tool is a list of statements. Data analysis techniques use percentages and product moment formulas. The results of the conclusions of this study indicate that (1) the learning needs of training participants at BBPPKS Padang based on all indicators are categorized as unfavorable. (2) the learning interest of training participants at BBPPKS Padang through all indicators is categorized as low. (3) The results of data processing show that there is a significant relationship between learning needs and the learning interests of training participants at BBPPKS Padang, this is proven and it is found that the results of rcount are greater than rtable.